2021
DOI: 10.1186/s13048-021-00845-6
|View full text |Cite
|
Sign up to set email alerts
|

Kinetics of HE4 and CA125 as prognosis biomarkers during neoadjuvant chemotherapy in advanced epithelial ovarian cancer

Abstract: Background Ovarian cancer (OC) is considered the most lethal gynecological cancer, of which more than 65% cases are diagnosed in advanced stages, requiring platinum-based neoadjuvant chemotherapy (NACT). Methods A prospective-longitudinal study was conducted among women with advanced epithelial ovarian cancer (AEOC), III and IV stages, and treated with NACT, at the National Cancer Institute – Mexico, from July 2017 to July 2018. Serum samples were … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 54 publications
0
9
0
Order By: Relevance
“…CA125 is a common biomarker in patients with ovarian cancer, which is of certain significance in diagnosis and prognosis. However, recent research showed that there was no significant correlation between CA125 and the efficacy of neoadjuvant chemotherapy in patients with ovarian cancer ( 7 ), necessitating the identification of biomarkers to predict the efficacy of neoadjuvant chemotherapy in ovarian cancer. The systemic immune-inflammation index (SII), reflecting the immune and inflammatory status of patients with malignant tumors, has been used in the diagnosis and treatment of a variety of malignant tumors and has been found to be related to the prognosis of patients ( 8 - 10 ).…”
Section: Introductionmentioning
confidence: 99%
“…CA125 is a common biomarker in patients with ovarian cancer, which is of certain significance in diagnosis and prognosis. However, recent research showed that there was no significant correlation between CA125 and the efficacy of neoadjuvant chemotherapy in patients with ovarian cancer ( 7 ), necessitating the identification of biomarkers to predict the efficacy of neoadjuvant chemotherapy in ovarian cancer. The systemic immune-inflammation index (SII), reflecting the immune and inflammatory status of patients with malignant tumors, has been used in the diagnosis and treatment of a variety of malignant tumors and has been found to be related to the prognosis of patients ( 8 - 10 ).…”
Section: Introductionmentioning
confidence: 99%
“…Ovarian cancer (OC) bears the highest mortality rate among gynecological malignancies [1]. At the time of diagnosis, 60-70% of patients present at an advanced stage, with a 5-year survival rate ranging between 20-30% [2]. Currently, clinical diagnosis and screening primarily rely on a combination of the serum tumor marker CA125 and transvaginal ultrasound.…”
Section: Introductionmentioning
confidence: 99%
“…Serum human epididymis secretory protein‐4 (HE4) is one of the most sensitive tumor markers of ovarian cancer found in recent years. Its serum level can be used as a good index to monitor the recurrence of ovarian cancer patients after chemotherapy 21 . The role of interleukin‐6 (IL‐6), tumor necrosis factor‐α (TNF‐α), and IFN‐γ in the development of ovarian cancer has attracted much attention 22 …”
Section: Introductionmentioning
confidence: 99%
“…Its serum level can be used as a good index to monitor the recurrence of ovarian cancer patients after chemotherapy. 21 The role of interleukin-6 (IL-6), tumor necrosis factor-α (TNF-α), and IFN-γ in the development of ovarian cancer has attracted much attention. 22 Therefore, this study compared the proportion of serum cytokines and T-lymphocyte subsets in recurrent and nonrecurrent epithelial ovarian cancer patients.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation